The influence of ESG scores on firm value: Audit quality as a moderation variable - Suranta, Eddy; Robinson, Robinson; Midiastuty, Pratana Puspa; Putra, Danang Adi; Fhatiana, Tiara Octa (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to provide empirical evidence of the influence of ESG scores on firm value (TobinsQ) and the influence of audit quality in moderating the influence of ESG on firm value. The population used in this study are companies that have ESG scores listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. This study uses a sampling technique, namely purposive sampling. The sample companies are non-financial companies that have ESG scores and present complete financial reports. The results of the study prove that the ESG Score has a positive effect on firm value, which means that the higher the ESG Score, the higher the risk that investors must accept, resulting in a decrease in the company's value. The results of the study further prove that audit quality moderates the influence of ESG on firm value. Quality can play an important role in increasing the credibility of financial reports from companies that have ESG scores so that audit quality provides accurate and reliable information about a company's ESG performance, which can be used by investors to make more informed investment decisions.